Development of a Defense Mechanisms Manual for Children's Doll Play (DMCP). (2nd January 2019) - Nimroody, Tehela; Hoffman, Leon; Christian, Christopher; Rice, Timothy; Murphy, Sean
ABSTRACT: Researchers have long recognized the richness of children's fantasy play and the ability of such play to reveal children's inner worlds and defensive structures. This article describes the development of The Defense Mechanisms Manual for Children's Doll Play (DMCP), a detailed and comprehensive manual that codes for 32 defense mechanisms in children's play. The levels of narrative coherence, creativity, and aggression in play narratives are also assessed. The manual draws on contemporary dream theory using the premise that the child narrator will disguise anxiety-provoking impulses through a number of defenses that can be discerned through the choices the child makes in creating the plot of the story. The manual was developed through the analysis of 30 sets of 10 story stems collected from 5- and 6-year-old children using the MacArthur Story Stem Battery, a structured story-completion task. Inter-rater reliability varied with the frequency of occurrence for each defense, ranging from excellent reliability for some measures to too few cases to assess for others. Cluster analyses of measures suggested four main clusters, loosely conceptualized as connecting to others, channeling aggression, avoidance, and symbolization.